2021
DOI: 10.1088/1361-6528/ac2f22
|View full text |Cite
|
Sign up to set email alerts
|

Design of high-quality reflectors for vertical III–V nanowire lasers on Si

Abstract: Nanowires (NWs) with a unique one-dimensional structure can monolithically integrate highquality III-V semiconductors onto Si platform, which is highly promising to build lasers for Si photonics. However, the lasing from vertically-standing NWs on silicon is much more difficult to achieve compared with NWs broken off from substrates, causing significant challenges in the integration. Here, the challenge of achieving vertically-standing NW lasers is systematically analysed with III-V materials, e.g. GaAs(P) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…III–V semiconductor heterostructures have a central role with diverse functionality in electronic and optoelectronic devices. Implementing such systems in freestanding nanowires could further broaden the scope of potential applications such as the design of complex quantum heterostructures, the management of light in nanoscale, the engineering of strain , or crystal structure, and the heterogeneous integration in technology-relevant platforms. It also raises expectations for on-demand photon sources (quantum dots and distributed Bragg reflectors hosted in the same nanowires) in quantum technology platforms. However, reducing the physical dimensions of heterostructures in nanotechnology devices toward atomic scales brings about a critical need for precise modulation of the chemical composition and effective management of the unintentional compositional grading across heterointerfaces.…”
Section: Introductionmentioning
confidence: 99%
“…III–V semiconductor heterostructures have a central role with diverse functionality in electronic and optoelectronic devices. Implementing such systems in freestanding nanowires could further broaden the scope of potential applications such as the design of complex quantum heterostructures, the management of light in nanoscale, the engineering of strain , or crystal structure, and the heterogeneous integration in technology-relevant platforms. It also raises expectations for on-demand photon sources (quantum dots and distributed Bragg reflectors hosted in the same nanowires) in quantum technology platforms. However, reducing the physical dimensions of heterostructures in nanotechnology devices toward atomic scales brings about a critical need for precise modulation of the chemical composition and effective management of the unintentional compositional grading across heterointerfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[19] This can be further enhanced using reflective layers designed for the lasing wavelength. [20] This reflectivity is strongly coupled to the mode confinement in the NW, and theoretical studies have shown that these relationships can be complex. [1] This is because optical far-field approximations are not valid when considering the behaviours of a sub-wavelength cavity -and as a result these effects are challenging to investigate experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…DBRs are used in a wide range of applications, such as optical feedback in single mode semiconductor lasers, Bragg grating filters and sensors [1,2]. Like their thin film counterparts, nanoscale devices can also benefit from DBRs [3][4][5][6][7]. In particular, vertically standing semiconductor nanowires (NWs) are known for their unique optical properties [8][9][10] arising from HE 1n leaky mode resonances (LMRs) [11].…”
Section: Introductionmentioning
confidence: 99%
“…n refers to the number of maxima in the mode intensity along a radial direction of the NW. Recently, there is increasing interest to implement DBRs into NW-based lasers [3][4][5], photovoltaics [6], and photonic bandgap applications [7]. However, the heterostructures required for conventional DBRs can be difficult to implement in NWs due to material diffusion, the 'reservoir effect' of the droplet seed particle [12,13], NW kinking [14,15], and other instabilities inherent to the nanoscale growth process.…”
Section: Introductionmentioning
confidence: 99%